Dispute Resolution of Sharia Gold Pawn in Indonesia - Dewi, Inggrid Kusuma; Nadirah, Ida (Universitas Muhammadiyah Tangerang, 2024)
Among the sharia economic products that are present in society are pawn products. However, of course sharia pawning must still be tested in an effort to improve the welfare of society. This research tries to find answers related to questions regarding the execution of collateral objects carried out by Sharia Banks or Sharia Pegadaian on customers' gold when gold prices are falling which can cause losses for customers. Apart from experiencing losses due to the sale of their gold which has a lower value, they also have to pay pawn deposit fees and other costs. For this reason, legal protection is needed for customers to prevent and overcome these problems. The suggestion that the researcher recommends is that regulations need to be made, a standard pawn system and socialization of sharia pawn products, which at the very least will be supported by the government. In the event of a dispute, mediation must be prioritized which refers to the teachings of Islamic law